2017
DOI: 10.3390/toxins9050162
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 Prevents Anthrax Lethal Toxin-induced Cell Cycle Arrest through Silencing PTEN in Human Monocytic THP-1 Cells

Abstract: Anthrax lethal toxin (LeTx) is a cytotoxic virulence factor that causes cell cycle arrest and cell death in various cell types. However, susceptibility to the cytotoxic effects varies depending on cell types. In proliferating monocytes, LeTx has only transient cytotoxic effects due to activation of the phosphoinositide 3-kinase (PI3K)-AKT-mediated adaptive responses. To date, the mechanism of LeTx in activating PI3K-AKT signaling axis is unknown. This study shows that the histone deacetylase 8 (HDAC8) is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Although the decrease in EZH2 expression in DU-145-luc treated xenografts (Figure 3) could explain in part the loss of H3K27me3 and perhaps there is a link between JMJD3 demethylase and PTEN that could explain these results. Two previous studies in monocytic cells and renal fibrosis have made comparable observations that support this hypothesis (49,50). We noted an effect of JMJD3 inhibition on PTEN expression with a slight decrease, but there was no impact on AKT expression between control and treated mice (Figure 3).…”
Section: Discussionsupporting
confidence: 84%
“…Although the decrease in EZH2 expression in DU-145-luc treated xenografts (Figure 3) could explain in part the loss of H3K27me3 and perhaps there is a link between JMJD3 demethylase and PTEN that could explain these results. Two previous studies in monocytic cells and renal fibrosis have made comparable observations that support this hypothesis (49,50). We noted an effect of JMJD3 inhibition on PTEN expression with a slight decrease, but there was no impact on AKT expression between control and treated mice (Figure 3).…”
Section: Discussionsupporting
confidence: 84%
“…GSK-J4 reduced type 1 diabetes incidence by protecting insulin-producing cells and human islets from cytokine-induced apoptosis and increasing expression of insulin gene and glucose-stimulated insulin secretion (Backe et al 2018). GSK-J4 also induced AKT activation and cell cycle arrest in human THP-1 cells treated with LeTx (Ha et al 2017). Treatment with GSK-J4 in human large B-cell lymphoma cell lines predominantly resulted in down rage of B-cell receptor signaling and BCL6 and introduced apoptosis of large B-cell lymphoma cells (Mathur et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that a combination of two or more drugs may benefit patients with anaplastic disease (Saini et al, 2018;Cao et al, 2019;Chintakuntlawar et al, 2019;Schurch et al, 2019). For example, combination sorafenib with quinacrine (Ha et al, 2017) and a combination of the BH3 mimic drug ABT-737 and doxorubicin (Ntziachristos et al, 2014) induced ATC cell apoptosis. Yong Sang Lee et al tested primary cells cultured from ATC patients and found that different combinations of HNHA (a histone deacetylase), lenvatinib (a fibroblast growth factor receptor inhibitor), and sorafenib (a tyrosine kinase inhibitor) were more effective than single drugs (Hjelmeland et al, 2017).…”
Section: Discussionmentioning
confidence: 99%